The genesys and base concepts of competentology - John R.; Korostelev A.A.; Yarygin O.N.; Mukhutdinov R.H.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This article presents the basic prerequisites for the development of a new discipline, which the authors called "competenceology". Due to the fact that now a phenomenon of competence is studied mainly within the so called competence approach in education (competence based education) and human resource management (HR), an unjustified reduction and distortion of the terminology and the understanding of the subject of research has appeared. The authors propose to consider competence as a phenomenon inherent not only to an individual, but also to an organization and society as a whole. This point of view is based on the historical analysis of scientific disciplines, investigating human activity. Considerable attention is devoted to the reconstruction of the "correct names" of the phenomena under consideration, that is, the terminology base of competence logy. As the main sources of competence logy the authors consider the praxeology (L.Mieses, T.Katorbinsky), the institutional theory of economic behavior (T.Veblen), materialistic philosophy and axiology (E.Fromm), modern psychology (J.Raven, M.Holodnaya), and also System Analysis and Sociocybernetics, based on the System Dynamics. The results of the authors's own research, which are partly presented in this article, allow to make an assumption about the effectivity of the approach under consideration in solving of the problems of the "incompetent society". BEIESP.